2019
DOI: 10.1016/j.chemgeo.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and nickel isotopes in seawater from the Indian Sector of the Southern Ocean: The impact of natural iron fertilization versus Southern Ocean hydrography and biogeochemistry

Abstract: The Southern Ocean is the site of 20% of global ocean carbon export, and the origin of water masses that significantly impact the chemistry of the global ocean. Much of the Southern Ocean is a high nutrient low chlorophyll (HNLC) region. Iron is the primary limiting nutrient for phytoplankton growth, and may also be an important control on the biogeochemistry of the water masses emanating from the Southern Ocean. Here we investigate the response of Zn and Ni and their isotopes to natural Fe fertilization from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
91
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(107 citation statements)
references
References 83 publications
13
91
0
Order By: Relevance
“…These deep-water values are consistent with other Southern Ocean deep-water ($700 m) measurements (e.g. Wang et al 2018), where mean (AE2s.d.) d 66 Zn dissolved was 0.40 AE 0.05% (n ¼ 13).…”
Section: Zinc Isotope Analysissupporting
confidence: 92%
“…These deep-water values are consistent with other Southern Ocean deep-water ($700 m) measurements (e.g. Wang et al 2018), where mean (AE2s.d.) d 66 Zn dissolved was 0.40 AE 0.05% (n ¼ 13).…”
Section: Zinc Isotope Analysissupporting
confidence: 92%
“…In the surface ocean, previous studies observed relatively low dissolved δ 66 Zn in almost all of the major oceanic regions with the exception of the SO. In the surface water of the SO, dissolved δ 66 Zn is comparable to or slightly isotopically heavier than the values observed in the deep water (Sieber et al, ; Wang et al, ; Zhao et al, ). A recent study in the subarctic Northeastern Pacific Ocean also observed some isotopically heavy signal in the surface water (Vance et al, ).…”
Section: Introductionmentioning
confidence: 63%
“…Spatial distribution patterns of Zn isotope composition (δ 66 Zn) would provide further insights in understanding its sources, sinks, and internal cycling processes in marine water column (Moynier et al, ). Recent studies on dissolved δ 66 Zn have provided further insight for Zn cycling in different oceanic regions, including the North Atlantic Ocean (Conway & John, ), the Southern Ocean (SO; Zhao et al, ; Sieber et al, ; Wang et al, ), the Southeastern Pacific Ocean (SEPO; John et al, ), and the Pacific Ocean (Bermin et al, ; Conway & John, ; John & Conway, ; Samanta et al, ; Vance et al, ). Several mechanisms have been proposed to explain the distribution of dissolved Zn elemental and isotopic composition in marine water column globally.…”
Section: Introductionmentioning
confidence: 99%
“…Combining the Ni data reported by Lai et al (2008) with the associated PO 4 for the upper water column (upper 300 m) [provided by Prof. Y. Sohrin (Kyoto University) and Prof. A. Bowie (University of Tasmania)], indeed the steepest slope (∼4.94 nmol µmol −1 ) is found for a station in summer in the PFZ, whereas less steep slopes are observed to the north and south, implying relatively high Ni uptake in the PFZ. However, this is based on a single station and, in contrast, a very gentle slope is found in the PFZ in spring over the Kerguelen plateau (Wang et al, 2019). Cloete et al (2019) also report an elevated Ni:PO 4 uptake ratio of >2 nmol µmol −1 at a single station, which they attributed to increased metal uptake by diatoms, but lower uptake ratios at other stations.…”
Section: Deep Distribution and Relationship With Nutrientsmentioning
confidence: 90%
“…The northern origin (NADW) and Antarctic origin (AAIW, uCDW, and AABW) deep water masses have different slopes for the Ni-PO 4 relationship (1.43 and 2.62 nmol µmol −1 , respectively), implying different uptake and remineralization ratios in the various source regions, as previously suggested for Zn and Cd. There is little data available for dissolved Ni in the high latitude oceans, but reported observations do suggest higher surface concentrations in the Southern Ocean [∼5 nmol kg −1 or higher (Lai et al, 2008;Butler et al, 2013;Cloete et al, 2019;Wang et al, 2019)] than in the open Arctic Ocean outside the Transpolar Drift [∼ 4 nmol kg −1 ; (Danielsson and Westerlund, 1983;Cid et al, 2012;Gerringa et al, unpublished)] or at the northern end of the current transect (Figure 2). The higher concentrations in the Southern Ocean are most likely due to upwelling of older deep water in this region whereas in contrast, the Arctic is largely supplied by nutrient poor surface water transported north with the Gulf stream [and only a modest amount of old (Pacific) water] (Van Aken, 2007).…”
Section: Deep Distribution and Relationship With Nutrientsmentioning
confidence: 99%